If so many are “few,” how few are “many”? - Heim, Stefan; McMillan, Corey T.; Clark, Robin; Golob, Stephanie; Min, Nam E.; Olm, Christopher; Powers, John; Grossman, Murray (Frontiers in Psychology, 2015)
The scope of reference of a word’s meaning can be highly variable. We present a novel paradigm to investigate the flexible interpretation of word meaning. We focus on quantifiers such as „many” or „few,” a class of words that depends on number knowledge but can be interpreted in a flexible manner. Healthy young adults performed a truth value judgment task on pictorial arrays of varying amounts of blue and yellow circles, deciding whether the sentence “Many/few of the circles are yellow” was an adequate description of the stimulus. The study consisted of two experiments, one focusing on „many”, one on „few.” Each experiment had three blocks. In a first “baseline” block, each individual’s criterion for „many” and „few” was assessed. In a second “adaptation” block, subjects received feedback about their decisions that was different from their initial judgments in an effort to evaluate the flexibility of a subject’s interpretation. A third “test” block assessed whether adaptation of quantifier meaning induced in block 2 then was generalized to alter a subject’s baseline meaning for „many” and „few.” In Experiment 1, a proportion of yellow circles as small as 40% was reinforced as „many”; in Experiment 2, a proportion of yellow circles as large as 60% was reinforced as „few”. Subjects learned the new criterion for „many” in Experiment 1, which also affected their criterion for „few” although it had never been mentioned. Likewise, in Experiment 2, subjects changed their criterion for „few”, with a comparable effect on the criterion for „many” which was not mentioned. Thus, the meaning of relational quantifiers like “many” and „few” is flexible and can be adapted. Most importantly, adapting the criterion for one quantifier (e.g. „many”) also appeared to affect the reciprocal quantifier (in this case, „few”). Implications of this result for psychological interventions and for investigations of the neurobiology of the language-number interface are discussed.